INVESTIGATING PATTERNS AND DETERMINANTS OF PHYSICAL ACTIVITY AND SEDENTARY BEHAVIOUR, THEIR EFFECTS ON BIOMARKERS OF RISK OF CARDIO-VASCULAR DISEASES AND DIABETES AND THEIR ASSOCIATION WITH URBANICITY IN A PERI-URBAN INDIAN POPULATION - EKTA JAIN (2020)
Ph.D